Biotic stress shifted structure and abundance of Enterobacteriaceae in the lettuce microbiome. - Armin Erlacher; Massimiliano Cardinale; Martin Grube; Gabriele Berg (PLoS ONE)
Lettuce cultivars are not only amongst the most popular vegetables eaten raw, they are also involved in severe pathogen outbreaks world-wide. While outbreaks caused by Enterobacteriaceae species are well-studied, less is known about their occurrence in natural environments as well as the impact of biotic stress. Here, we studied the ecology of the human health-relevant bacterial family Enterobacteriaceae and assessed the impact of biotic disturbances by a soil-borne phytopathogenic fungus and Gastropoda on their structure and abundance in mesocosm and pot experiments. Using a polyphasic approach including network analyses of 16S rRNA gene amplicon libraries, quantitative PCR and complementary fluorescence in situ hybridization (FISH) microscopy we found substantial yet divergent Enterobacteriaceae communities. A similar spectrum of 14 genera was identified from rhizo- and phyllospheres but the abundance of Enterobacteriaceae was on average 3fold higher in phyllosphere samples. Both stress factors shifted the bacterial community of the leaf habitat, characterized by increases of species abundance and diversity. For the rhizosphere, we observed significant structural shifts of Enterobacteriaceae communities but also a high degree of resilience. These results could be confirmed by FISH microscopy but it was difficult to visualize phyllosphere communities. Additional inoculation experiments with Escherichia coli as model revealed their presence below the wax layer as well as in the endosphere of leaves. The observed presence influenced by stress factors and the endophytic life style of Enterobacteriaceae on lettuce can be an important aspect in relation to human health.